Can a Self-etching Primer be Effective in Bonding Aligner Attachments to Different Types of Ceramics? - Serpil Çokakoğlu; Ruhi Nalçacı; Subutay Han Altıntaş; Fatih Atıcı (Galenos Yayinevi, 2024)
Objective: This in vitro study aimed to evaluate the effectiveness of pretreatment with a self-etching primer for bonding aligner attachments to lithium disilicate (LD) and monolithic zirconia (MZ) ceramics. Methods: Forty ceramics, including LD (n=20) and MZ (n=20), were divided into four study groups according to the surface pretreatments: LD specimens pretreated with universal primer (Monobond Plus, MP) after hydrofluoric acid etching (Group 1); MZ ceramics pretreated with MP after sandblasting (Group 2); LD ceramics pretreated with self-etching ceramic primer (Monobond etch & prime, MEP) (Group 3); and MZ ceramics pretreated with MEP after sandblasting (Group 4). The aligner composite (GC Aligner Connect) and universal adhesive (GPremio Bond) were used to prepare the resin attachments. The bond strength was evaluated by micro-shear bond strength (SBS) testing (0.1 mm/min) after thermocycling, and the remnant adhesive was scored according to the resin attachment remnant index (RARI). The SBS data were analyzed using ANOVA and Tukey tests, and the RARI scores were analyzed using the chi-square test. Results: Group 1 had the lowest SBS, and group 2 had the highest SBS. There were significant differences between the groups in terms of bond strength (p<0.05). The RARI scores showed no significant differences, regardless of the pretreatment and ceramic type. Conclusion: The use of a self-etching primer increased the bond strength of resin attachments on LD ceramics. For zirconia ceramics, both ceramic primers are recommended for aligner attachment bonding.